2020
DOI: 10.7150/jca.33527
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Interferon-Tau Activates Type I interferon-Associated Janus-signal Transducer in HPV16-positive Tumor Cell

Abstract: The mechanisms of signal transduction by interferon-tau (IFN-τ) are widely known during the gestation of ruminants. In trophoblast cells, IFN-τ involves the activation of the JAK-STAT pathway, and it can have effects on other cell types, such as tumor cells. Here we report that the HPV16-positive BMK-16/myc cell treated with ovine IFN-τ, results in the activation of the canonical JAK-STAT and non-canonical JAK-STAT pathway. The MAPK signaling pathway was activated, we detected the proteins MEK1, MEK2, Raf1, ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that IFN-τ induces an antiproliferative effect and apoptosis in HPV-16 transformedcells; they also showed tumor growth inhibition in an HPV-16positive murine tumor model (11). Moreover, the effects of IFNτ on tumor cells were associated with the MHC Class I, MX and IP10 gene expression (12). However, immunoregulatory mechanisms associated with the antitumor effect of IFN-τ have not yet been studied.…”
Section: Interferon-tau (Ifn-τ) Has Antiproliferative Effectsmentioning
confidence: 99%
“…Previous studies have shown that IFN-τ induces an antiproliferative effect and apoptosis in HPV-16 transformedcells; they also showed tumor growth inhibition in an HPV-16positive murine tumor model (11). Moreover, the effects of IFNτ on tumor cells were associated with the MHC Class I, MX and IP10 gene expression (12). However, immunoregulatory mechanisms associated with the antitumor effect of IFN-τ have not yet been studied.…”
Section: Interferon-tau (Ifn-τ) Has Antiproliferative Effectsmentioning
confidence: 99%